Revisiting Speed Management Strategies in Malaysia - Ab Rashid, A.A.; Poi, A.W.H.; Jawi, Z.M.; Abu Kassim, K.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Speed, because of its centrality to mobility, deserves effective management approaches. This review examined the present approaches in Malaysia: speed zoning, enforcement, education, and physical engineering; before putting forward evidence of their limited effectivity. The discussion continued with a proposal for preventive approaches in managing speed. Instead of reactive measures, i.e. curbing the speeding, the proposal clutches on the elimination of room for speeding by advocating for vehicular speed management system – e.g. the intelligent speed adaptation technology, or top speed limiting by design. The potential regulatory mechanism, implementation challenges, and subsequent courses of action to realize the proposal concludes the article.